The Prevalence of Gingival Dendritic Cell Subsets in Periodontal Patients. (November 2021) - Sharawi, H.; Heyman, O.; Mizraji, G.; Horev, Y.; Laviv, A.; Shapira, L.; Yona, S.; Hovav, A.H.; Wilensky, A.
As the most potent cells activating and polarizing naive T cells, dendritic cells (DCs) are of major importance in the induction of immunity and tolerance. DCs are a heterogeneous population of antigen-presenting cells that are widely distributed in lymphoid and nonlymphoid tissues. Murine studies have highlighted the important role of oral DCs and Langerhans cells (LCs) in orchestrating the physiological homeostasis of the oral mucosa. DCs are also critically involved in pathological conditions such as periodontal diseases, in which gingival DCs appear to have special localization and function. While the characterization of human DCs in health and disease has been extensively investigated in various tissues, this topic was rarely studied in human gingiva. Here, we employed an up-to-date approach to characterize by flow cytometry the gingival DCs of 27 healthy subjects and 21 periodontal patients. Four distinct subsets of mononuclear phagocytes were identified in healthy gingiva: conventional DC type 1 (cDC1), cDC2, plasmacytoid DCs (pDCs), and LCs. In periodontitis patients, the frequencies of gingival LCs and pDCs were dysregulated, as LCs decreased, whereas pDCs increased in the diseased gingiva. This shift in the prevalence of DCs was accompanied by increased expression of the proinflammatory cytokines interleukin (IL)–1β, interferon (IFN)–α, and IFN-γ, while the anti-inflammatory cytokine IL-10 was suppressed. We further found that smoking, a known risk factor of periodontitis, specifically reduces gingival LCs in healthy individuals, indicating a possible role of LCs in the elevated severity of periodontitis in smokers. Collectively, this work reveals the various DC subsets residing in the human gingiva and the impact of periodontitis, as well as smoking, on the prevalence of each subset. Our findings provide a foundation toward understanding the role of human DCs in orchestrating physiological oral immunity and set the stage for the evaluation and modulation of shifts in immunity associated with periodontitis.